2018
DOI: 10.1038/s41419-017-0204-3
|View full text |Cite
|
Sign up to set email alerts
|

circHIPK3 regulates cell proliferation and migration by sponging miR-124 and regulating AQP3 expression in hepatocellular carcinoma

Abstract: Noncoding RNAs plays an important role in hepatocellular carcinoma (HCC). Here, we show that miR-124 was downregulated in HCC tissues and that the ectopic expression of miR-124 inhibited the proliferation and migration of HCC cells. We proposed that aquaporin 3 (AQP3) is a direct target of miR-124. AQP3 was upregulated in HCC tissues and inversely correlated with miR-124 expression. The overexpression of miR-124 decreased AQP3 expression. Indeed, AQP3 overexpression promoted cell proliferation and migration, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(198 citation statements)
references
References 39 publications
3
191
4
Order By: Relevance
“…circMTO1 suppresses HCC proliferation and invasion by sponging miR‐9 and upregulating the downstream p21 . circHIPK3 facilitates HCC progression through serving as a miR‐124 sponge and subsequently modulating AQP3 in HCC . Given the cytoplasmic location of circLARP4, we speculated that circLARP4 might function as a miRNA sponge to dampen HCC malignant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…circMTO1 suppresses HCC proliferation and invasion by sponging miR‐9 and upregulating the downstream p21 . circHIPK3 facilitates HCC progression through serving as a miR‐124 sponge and subsequently modulating AQP3 in HCC . Given the cytoplasmic location of circLARP4, we speculated that circLARP4 might function as a miRNA sponge to dampen HCC malignant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased AQP3 expression was found in HCC and was negatively correlated with miR‐124 expression. AQP3 could be reduced by overexpressing miR‐124, thereby inhibiting the proliferation and migration of hepatoma . Another HCC‐related study demonstrated that miR‐124 could further inhibit the proliferation of HCC cells (SMMC‐7721) by regulating Baculoviral IAP Repeat Containing 3 (BIRC3) and controlling the NF‐kB pathway and migration.…”
Section: Mir‐124 and Hepatocellular Carcinomamentioning
confidence: 99%
“…Based on RNA‐sequence technology, Zheng et al discovered that circ HIPK3 (hsa_circ_0000284) is significantly upregulated in liver cancer compared with matched normal tissues and directly binds to miR‐124, thereby upregulating Interleukin 6 receptor (IL6R) and Homeobox protein DLX2 expression. Chen et al discovered that hsa_circ_0000284 promotes HCC proliferation and migration by directly binding to miR‐124, thereby upregulating aquaporin 3 (AQP3) expression. By sponging miR‐17‐3p and miR‐181b‐5p, hsa_circ_0001445 promotes the expression of metalloproteinase inhibitor 3 (TIMP3) and then inhibits the proliferation and migration of HCC cells .…”
Section: Circrnas and Hccmentioning
confidence: 99%